2021
DOI: 10.1038/s41598-021-88918-w
|View full text |Cite
|
Sign up to set email alerts
|

The development of structural covariance networks during the transition from childhood to adolescence

Abstract: Structural covariance conceptualizes how morphologic properties of brain regions are related to one another (across individuals). It can provide unique information to cortical structure (e.g., thickness) about the development of functionally meaningful networks. The current study investigated how structural covariance networks develop during the transition from childhood to adolescence, a period characterized by marked structural re-organization. Participants (N = 192; scans = 366) completed MRI assessments be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 78 publications
3
19
0
Order By: Relevance
“…Poor segregation and higher integration have previously been related to other psychiatric and neurological conditions [44], including dependence on alcohol and other substances [16–18]. Typically, segregation peaks by late adolescence and young adulthood, probably reflecting functional specialization among cortical regions [44,45]. Therefore, we speculate that our results suggest a protracted cortical maturation in the alcohol‐drinking groups [13,42,46].…”
Section: Discussionmentioning
confidence: 54%
“…Poor segregation and higher integration have previously been related to other psychiatric and neurological conditions [44], including dependence on alcohol and other substances [16–18]. Typically, segregation peaks by late adolescence and young adulthood, probably reflecting functional specialization among cortical regions [44,45]. Therefore, we speculate that our results suggest a protracted cortical maturation in the alcohol‐drinking groups [13,42,46].…”
Section: Discussionmentioning
confidence: 54%
“…Third, the complementary analyses implied DAN as the candidate functional system associated with PatAGE. It should be noted that the brain atlases and public datasets implemented in Neurosynth are primarily from research on adults, while children have specific characteristics regarding brain organization (Tooley et al, 2021;Vijayakumar et al, 2021). We tempted to address this issue by adopting the functional network template for children in analyzing diffusion imaging data available in a subgroup of the current samples and found that the PatAGE-cluster more strongly connected with DAN than VAN.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Given that the functional community structure in children is to some extent different from that in adults and the highest uncertainty was found in attention networks (Tooley, Bassett, & Mackey, 2021;Vijayakumar et al, 2021), in the final step, we examined the structural connectivity pattern in a sub-group of our own samples where diffusion imaging data were available. Moreover, we adopted a pediatric intrinsic functional network template that was extracted from 670 children aged 9-11 years (Tooley et al, 2021) with the same approach as in Yeo et al (2011).…”
Section: Thalamus Mediates Patage Effect On Reading 20mentioning
confidence: 99%
“…Therefore, the analysis of structural covariance may provide complementary information to fMRI and diffusion tensor imaging (DTI) networks and help to further clarify the specific mechanisms that underlie neurological and psychiatric disorders. Thus far, structural covariance analysis has successfully been used to explore changes in the anatomical coupling of healthy subjects and patients with various psychiatric and neurological disorders, such as schizophrenia, major depressive disorder, Parkinson's disease, and Alzheimer's disease [ 14 , 16 22 ].…”
Section: Introductionmentioning
confidence: 99%